Environmental Journalism on Primate Conservation and Owa Coffee Reporting : An Autoethnography - Aditya Heru Wardhana (Universitas Multimedia Nusantara, 2024)
Global coffee consumption continues to increase, but the threat of climate change is real and felt in the quality and quantity of coffee production. Indonesia as one of the coffee producing countries also faces problems caused by various factors, one of which is land conversion. Since 2008, Yayasan SwaraOwa has been running the Coffee and Primate Conservation Project in Pekalongan, Central Java, Indonesia. The project's goal is to establish sustainable conservation efforts for Javan gibbons by establishing small to medium-sized businesses for the local communities that surround the gibbon forest. Kopi Owa, or Owa coffee, is the brand that created with the goal of promoting shade-grown coffee as a forest product that comes from the Javan gibbon's habitat. CNN Indonesia reported on the Javan Gibbon conservation program and the transformation of communities from loggers and poachers to coffee farmers in documentary, feature article and photo series formats. This research uses autoethnographic methods to explain the pre-production, production and post-production processes of environmental journalism on Owa coffee, primate conservation, and community economic empowerment reporting.